The importance of calcium in the immunity of the body in chickens - Al-Azawi, Tahani S. S. (The Iraqi Journal of Veterinary Medicine, 2003)
Blood samples were obtained from clinically normal Fawbro chicks in order to study age – related blood changes in lymphocytes, globulin and calcium percentage. A total of 30 Fawbro chicks were kept from the first day of hatching till the fifty sixth day in one room and were fed on commercial starter and finisher rations. Two blood samples were taken from jegular or wing vein every week. One sample was used for total and differential leukocytic count, the other sample was used for serum isolation to estimate total protein, globulin and calcium amount, total plasma calcium estimation. The results of this study provide an important reference and appear to be the first set of published data for the age – related blood values concerned with immunity in chickens. The important role of calcium in immunity is also reported and discussed here for the first time.